Behaviour of captive Canvasbacks Aythya valisineria fed different diets during winter - Perry, Matthew C; Williams, Byron K; Obrecht, Holliday H, III (Wildfowl, 1989)
Time activity budget studies were conducted on captive Canvasbacks maintained on adlibitum diets with varying levels of protein and energy during the winters of 1978-79 and 1979-80. No differences could be detected in the behaviour of the ducks as a result of the diets they received. Differences due to season and sex were observed for some behaviours. Activity decreased (P<0.05) during the winter apparently as a mechanism to conserve energy. This decrease occurred in mid-winter irrespective of diet quality and appeared to be an endogenous component of the Canvasbacks’ annual cycle. This behaviour pattern has been observed in the wild and seems to persist in captive Canvasbacks.